2015
DOI: 10.1016/j.cellimm.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ CD44v.low cells are unique peripheral precursors that are distinct from recent thymic emigrants and stem cell-like memory cells

Abstract: CD4+ CD44v.low cells are peripheral precursor T cells that inhibit lymphopenia by generating a large CD4+ T cell pool containing balanced numbers of naïve, memory, and regulatory Foxp3+ cells with a diverse TCR repertoire. Recent thymic emigrants (RTE) and stem cell-like memory T cells (TSCM) can also replenish a T cell pool. In this study we formally test whether CD44v.low cells are the same population as RTE and TSCM. Our data show that, in contrast to RTE, CD44v.low cells express high levels of CD45RB and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Previously published work from our group has shown that injecting CD4 + precursor T cells into mice with cancer can both re‐establish balanced numbers of naïve, memory, and regulatory T cells and protect from muscle wasting . To our knowledge, these data were the first to show a link between muscle health and T cell homeostasis in mice.…”
Section: Introductionsupporting
confidence: 52%
“…Previously published work from our group has shown that injecting CD4 + precursor T cells into mice with cancer can both re‐establish balanced numbers of naïve, memory, and regulatory T cells and protect from muscle wasting . To our knowledge, these data were the first to show a link between muscle health and T cell homeostasis in mice.…”
Section: Introductionsupporting
confidence: 52%
“…Also both strains had an increase in CD62L high CD44 very low cells. This subset is reported to be enriched for naïve CD4 T cells with stem cell-like properties 27 . We checked the responsiveness of DN thymocytes to CXCL12 and CCL19 and mature SP CD4 thymocytes to the same chemokines and to S1P.…”
Section: Resultsmentioning
confidence: 99%
“…Cell subsets with a Th2 bias have been noted previously and include recent thymic emigrants (RTE) [34] and CD4 + CD44 v.low peripheral precursor cells [35]. We have ruled out the possibility that CD25 + CD127 hi cells are either RTE or CD44 v.low precursor cells because they do not express the naïve cell marker, CD45RA.…”
Section: Discussionmentioning
confidence: 96%